Forecasting Uses of Anticipatory Data: Comment - Anderson, W. H. Locke (Quarterly Journal of Economics, 1959)
Journal Article Forecasting Uses of Anticipatory Data: Comment Get access W. H. Locke Anderson W. H. Locke Anderson Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 73, Issue 1, February 1959, Pages 169–170, https://doi.org/10.2307/1883831 Published: 01 February 1959